Znaczenie regulacji celnych Wspólnot Europejskich dla podmiotów gospodarczych w Polsce - Drelich-Skulska, Bogusława (Significance of the European Communities' Customs Regulations for Businesses in Poland, 2005)
Poland's access to the European Union necessitated the introduction of the European Communities' Customs Code and its executory regulations into the business practice of Poland as of 1 May 2004. This publication aims at presenting the significance of the community customs regulations for the Polish businesses. Following the community regulations with respect to customs affairs will prove a considerable challenge both for the businesses and customs authorities in Poland. Undoubtedly, the practice developed in other member states will help in the correct interpretation of regulations and in the identification of all the possibilities related to the EU extension. As a result of the access to the EU, Polish businessmen have to face stronger competition not only from the community producers, but also from the suppliers from third countries, due to a lower degree of customs protection and extensive system of customs preferences applied by the Community. At the same time Polish businessmen will be able to take the advantage of the protection from unfair competition from third countries by means of the protection, antidumping and antisubsidy proceedings. The nearest future will show what is the actual level of preparation of Polish businesses and customs authorities for the trading of goods with the partners from the European Union and from third countries in the new economic reality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 76-85